Political Education for High School Students in Makassar City - Handam; Muchlas M Tahir (Journal La Edusci, 2020)
This article aims to discuss the political activity of beginner voter education for high school students to realize the awareness of novice voters to participate in elections, understanding the importance of the role of novice voters in the democratic process, and knowledge of political developments for novice voters. The results achieved are the emergence of student enthusiasm in discussing matters related to political issues. It is quite visible that this is marked by the topics they discuss about elections that produce trustworthy leaders and then enlightenment given in understanding the importance of novice voters in participating the election was well received and the enthusiasm for conducting the election received a positive response from the students, but it was interesting because it turned out that students' understanding of the general election was more influenced by the media they watched such as TV and social media